Social and economic benefits of cultural heritage tourism in the city of Shumen (Research Announcements "Heritage BG", 2025)
The goal of this study is to reveal the social and economic benefits of heritage tourism in the city of Shumen in 2021. The focus is on the perceptions of Bulgarian tourists as there were almost no foreign visitors due to the pandemic situation. The research is based on data through a standardized questionnaire from 508 visitors to five significant heritage sites (Madara Rider, Shumen Fortress, ‘Founders of the Bulgarian State’, Tombul Mosque, and Regional History Museum). The study seeks to answer the following research questions: (1) What are the motives for visiting, impressions, evaluations and recommendations of visitors to these sites? (2) What are the economic benefits for the heritage sites and the city? The results show that domestic heritage tourists benefit mainly from a good combination of culture and beautiful nature, while the heritage sites could not sustain only from their own revenue and need additional support. References:Program for the development of tourism in the municipality of Shumen 2018 – 2021 (In Bulgarian). Retrieved from: https://obs.shumen.bg/decisions/1886903.pdfAdie, Hall 2017: Adie, Bailey Ashton, Hall, C. Michael. Who Visits World Heritage? A Comparative Analysis of Three Cultural Sites. Journal of Heritage Tourism, 12(1), 67-80. https://doi:10.1080/1743873X.2016.1151429.Antуn et al. 2017: Antуn, Carmen, Camarero, Carmen, Laguna-Garcнa, Marta. Towards a New Approach of Destination Loyalty Drivers: Satisfaction, Visit Intensity and Tourist Motivation. Current Issues in Tourism, 20(3), 238 – 260. https://doi.org/10.1080/13683500.2014.936834.Ashworth 2008: Ashworth, Gregory. How do Tourists Consume Heritage Places? In: Lehtimдki, M. (ed.): Cultural Heritage and Tourism. Potential, Impact, Partnership and Governance. A book on cultural heritage and tourism to inspire policy makers and practitioners at all levels, proceedings of the III Baltic Sea Region Cultural Heritage Forum, Vilnius, 25 – 27 September 2007. Vilnius, 52 – 58.Ashworth, Tunbridge 1990: Ashworth, Gregory, Tunbridge, John. The Tourist-Historic City. London: Belhaven Press.Cristofle 2012: Cristofle, Sylvie. Patrimoine culturel, tourisme et marketing des lieux : Nice et la Cфte d’Azur entre dйsirs de territoire et dйveloppement. In: Fournier, L. S., Crozat, D., Berniй-Boissard, C., & Chastagner, C. (Eds.). Patrimoine et valorisation des territoires. Paris: L’Harmathan, 17-36. https://doi:hdl.handle.net/10400.12/133.Di Pietro, Mugion, Renzi 2014: Di Pietro, Laura, Mugion, Roberta Guglielmetti, Renzi, Maria Francesca. Cultural Technology District: A Model for Local and Regional Development. Current Issues in Tourism, 17(7), 640 – 656. https://doi.org/10.1080/13683500.2013.789006Halpenny et al. 2018: Halpenny, Elizabeth, Kono, Shintaro, Moghimehfar, Farhad. Predicting World Heritage Site Visitation Intentions of North American Park Visitors. Journal of Hospitality and Tourism Technology, 9(3), 417 – 437. https://doi.org/10.1108/JHTT-10-2017-0109.Kempiak et al. 2017: Kempiak, Joanna, Hollywood, Lynsey, Bolan, Peter, McMahon-Beattie, Una. The Heritage Tourist: An Understanding of the Visitor Experience at Heritage Attractions. International Journal of Heritage Studies, 23(4), 375 – 392, https://doi.org/10.1080/13527258.2016.1277776.Lуpez-Guzmбn et al. 2018: Lуpez-Guzmбn, Tomas, Gбlvez, Jesъs Claudio Pйrez, Fernбndez, Guzmбn Antonio Muсoz, Leуn, Leonardo Torres. Studying World Heritage Visitors: The Case of Cuenca, Ecuador. Journal of Cultural Heritage Management and Sustainable Development, 8(3), 372 – 386. https://doi.org/10.1108/JCHMSD-03-2018-0017Marinov et al. 2020: Marinov, Vasil, Assenova, Mariana, Nikolova, Vera, Kazakov, Atanas, Mitova, Radenka, Petkova, Elena. Profile of Visitors to Cultural Heritage Attraction in Bulgaria. Proceedings of the 6th International Scientific Conference GEOBALCANICA 2020 (12-14 May). http://dx.doi.org/10.18509/GBP.2020.44.Ramires et al. 2018 : Ramires, Ana, Brandao, Filipa, Sousa, Ana Cristina. Motivation-based Cluster Analysis of International Tourists Visiting a World Heritage City: The Case of Porto, Portugal. Journal of Destination Marketing and Management, 8, 49 – 60. http://doi.org/10.1016/j.dmm.2016.12.001.Remoaldo et al. 2014a: Remoaldo, Paula C., Ribeiro, Josй C., Vareiro, Laurentina, Santos, Josй F. Tourists’ Perceptions of World Heritage Destinations: The Case of Guimarгes (Portugal). Tourism and Hospitality Research, 14(4), 206 218. https://doi.org/10.1177/1467358414541457.Remoaldo et al. 2014b: Remoaldo, Paula C., Vareiro, Laurentina, Ribeiro, Josй C., Santos, Josй F. Does Gender Affect Visiting a World Heritage Site? Visitor Studies, 17(1), 89 – 106. https://doi.org/10.1080/10645578.2014.885362.Ritchie, Hudson 2009: Ritchie, J.R. Brent, Hudson, Simon. Understanding and Meeting the Challenges of Consumer/Tourist Experience Research. International Journal of Tourism Research, 11(2), 111 – 126. https://doi.org/10.1002/jtr.721.UNWTO 2018: United Nations World Tourism Organization. Tourism and Culture Synergies, Madrid. Retrieved from: https://www.e-unwto.org/doi/epdf/ 10.18111/9789284418978 (01.10.2022).
Keywords: Shumen; heritage sites; domestic tourists; motives; benefits